EFL Students’ Understanding of Moral Values in Reading English Narrative Text - Novita sari; Ahmad Laut Hasibuan; Annisa Zahra Hasibuan; Nazriani Lubis (Indonesian Journal of ELT and Applied Linguistics, 2023)
This research deals with students' understanding of moral values ​​in English narrative texts. This research was conducted by students’ of SMP IT Nurul Ikhwan Pantai Cermin. This research focused on "what moral values ​​are understood by students after reading the narrative text and analyzing the moral values ​​contained in the narrative text. This research aimed to analyzed what moral values understood by students that were consisted of patience, kindness, helpful and humbleness. The method used in this research is qualitative method. The subjects of the research were 9 students and they divided into 3 groups: students with higher reading comprehension, students with moderate reading comprehension and students with lower reading comprehension. Technique of collecting the data was done by providing narrative texts that have moral values ​​to students, researchers provided questions related to moral values ​​and then researchers determine students' understanding of moral values. From the results of data collection it was concluded that there are still many students who did not understand the moral values ​​in narrative texts due to lacked of English vocabulary and lacked of understanding of information contained in English texts